2020
DOI: 10.1039/d0nr04179c
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism of the surface functionalization dependent neurotoxicity of graphene family nanomaterials

Abstract: Graphene family nanomaterials (GFNs) have shown great potential for biological and environmental applications; however, their future use has been debated due to reported potential neurotoxicity. Moreover, the effects of surface...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Our results exclusively showed that hydroxylation endows the GQDs with higher phytotoxicity than the other two functionalizations, with the lowest phytotoxicity arising from the aminated GQDs. Although there is no data in plant systems available for a comparison with our data, our results agree with some previous studies using cell lines, [18] bacteria [19] and fish [20] that aminated graphene or GQDs usually have lower toxicity than carboxylated and hydroxylated ones. Our data showed that surface functionalization dependent toxicity was not only observed for phenotypical data such as seedling length and biomass, but also for physiological response including impairment of photosynthesis and triggering of antioxidant defence and phytohormone regulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results exclusively showed that hydroxylation endows the GQDs with higher phytotoxicity than the other two functionalizations, with the lowest phytotoxicity arising from the aminated GQDs. Although there is no data in plant systems available for a comparison with our data, our results agree with some previous studies using cell lines, [18] bacteria [19] and fish [20] that aminated graphene or GQDs usually have lower toxicity than carboxylated and hydroxylated ones. Our data showed that surface functionalization dependent toxicity was not only observed for phenotypical data such as seedling length and biomass, but also for physiological response including impairment of photosynthesis and triggering of antioxidant defence and phytohormone regulation.…”
Section: Discussionsupporting
confidence: 92%
“…[ 33 ] Similarly, hydroxylated graphene showed higher acute neurotoxicity on human neuroblastoma cells than carboxylated and aminated graphene; however, the study also showed that aminated graphene caused more persistent toxicity than the other two functionalization. [ 18 ] These results indicate that longer‐term study may be necessary in the future. In addition, a recent study showed that 1–10 mg L −1 GQDs caused persistent toxicity to the photosynthesis of green algae ( Chlorella vulgaris ) which play a vital role in maintaining the food web in aquatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…More than a few decades have passed since the application of nanomaterials (NMs) in medicine and since the concept of nanotoxicity was formulated ( 1 ). Despite the time lapsed, concerns regarding their potential neurotoxicity ( 2 ) have yet to be fully addressed, primarily because of challenges in characterization resulting from their unique physicochemical properties. Recent studies found NMs (e.g., ZnO and magnetite NMs) can accumulate in the brain with distinct morphologies and forms that differ from their pristine counterpart, which can affect the cholinergic neurotransmission and thus brain health ( 3 , 4 ).…”
mentioning
confidence: 99%
“…The sample was redissolved in 100 µl of acetonitrile/water (1:1, v/v), adequately vortexed, and then centrifuged (18,800 g , 4°C, 15 min). The supernatant was collected for LC‐MS/MS analysis (Guo et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%